Symptomatic adrenal insufficiency during inhaled corticosteroid treatment. Issue 4 (1st October 2001) - Patel, L; Wales, J K; Kibirige, M S; Massarano, A A; Couriel, J M; Clayton, P E
Abstract : Symptomatic adrenal insufficiency, presenting as hypoglycaemia or poor weight gain, may occur on withdrawal of corticosteroid treatment but has not previously been reported during inhaled corticosteroid treatment. This case series illustrates the occurence of clinically significant adrenal insufficiency in asthmatic children while patients were on inhaled corticosteroid treatment and the unexpected modes of presentation. General practitioners and paediatricians need to be aware that this unusual but acute serious complication may occur in patients treated with inhaled corticosteroids.